Academic skills problems : direct ssessment and intervention - Shapiro, Edward S. (The Guildford school practitioner series, 1996)
(from the jacket) This popular practitioner guide and text presents an effective, problem-solving-based approach to evaluating and remediating academic skills problems. Leading authority Edward S. Shapiro provides practical strategies for working with students across all grade levels (K-12) who are struggling with reading, spelling, written language, or math. Incorporating the latest advances in evidence-based assessment and instruction, the fourth edition shows how the author's model fits perfectly into a response-to-intervention (RTI) framework. Shapiro emphasizes the importance of evaluating academic skills in the context of the school curriculum. He offers step-by-step guidelines for assessing students' learning and their instructional environment through the use of systematic observation, rating scales, teacher and student interviews, examination of student-produced work, and skills probes. The book explains how to integrate and use the resulting data to design appropriate instructional modifications. It also describes progress monitoring procedures for determining both the short- and long-term outcomes of interventions. Research supporting the approach is clearly summarized. Special features include helpful figures, tables, and sample forms--many of which are new or revised--as well as in-depth case examples. A new chapter and case example in the fourth edition focus specifically on direct assessment and intervention within RTI. The companion workbook, available separately, contains practice exercises and reproducible forms. Grounded in current knowledge and best practices, this authoritative volume belongs on the desks of school psychologists, school administrators, special educators, and classroom teachers. It will serve as a text in graduate-level courses dealing with academic assessment and intervention.